2008
DOI: 10.1007/s11947-008-0063-0
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Production from Biodegradation of Creosote Bush Ellagitannins by Aspergillus niger in Solid State Culture

Abstract: The ability of Aspergillus niger GH1 in converting creosote bush ellagitannins into ellagic acid (EA) was evaluated in solid state culture. Creosote bush leaves were used to extract the ellagitannins fraction, which was impregnated in polyurethane foam used as support of solid state culture. Ellagitannins content, EA accumulation, and the related enzymatic activities were evaluated. A. niger GH1 was able to completely degrade creosote bush ellagitannins with an EA yield of 23.1% at 36 h of culture. The ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…EAHp values obtained in this study are notable promising compared to those previously reported for A. niger SHL 6 using valonea tannins as a carbon source in liquid culture, reaching values of 0.92 U L -1 h -1 (Huang et al, 2007). Also, Aguilera-Carbó et al (2009) reported the production of ellagic acid from creosote bush by A. niger GH1 obtaining an EAH p of 1.22 U L -1 h -1 . In a different work in which was used A. niger GH1, PUF as support and pomegranate extracts as carbon source produced an EAHp of 0.92 U L -1 h -1 (Aguilera-Carbó, 2009).…”
Section: Ea Production Under Ssf Conditionssupporting
confidence: 74%
“…EAHp values obtained in this study are notable promising compared to those previously reported for A. niger SHL 6 using valonea tannins as a carbon source in liquid culture, reaching values of 0.92 U L -1 h -1 (Huang et al, 2007). Also, Aguilera-Carbó et al (2009) reported the production of ellagic acid from creosote bush by A. niger GH1 obtaining an EAH p of 1.22 U L -1 h -1 . In a different work in which was used A. niger GH1, PUF as support and pomegranate extracts as carbon source produced an EAHp of 0.92 U L -1 h -1 (Aguilera-Carbó, 2009).…”
Section: Ea Production Under Ssf Conditionssupporting
confidence: 74%
“…Punicalagin and punicalin from pomegranate husk [ 76 ] have been reported as an optimal carbon source for EA production by Aspergillus niger GH1, by solid-state fermentation, using a polyurethane foam support [ 75 ]. Several studies have attempted to optimize the process for EAH and EA [ 77 , 78 ]. There were also studies that encourage the use of immobilized systems (simulating an immobilization process using fermented solids) in order to improve productivity and efficiency [ 79 , 80 ].…”
Section: Production Of Ellagic Acidmentioning
confidence: 99%
“…High concentrations of gallic and ellagic acids were also obtained by Aspergillus niger PSH during SSF of tannin-rich aqueous extracts from Larrea tridentata impregnated in polyurethane foam . Aspergillus niger GH1 has also been reported as being a fungi with great ability to hydrolyze ellagitannins into ellagic acid during SSF using Larrea tridentata as substrate (Aguilera-Carbo et al, 2009).…”
Section: Production and Extraction Of Bioactive Phenolic Compounds Frmentioning
confidence: 99%